29 Alivecor: detecting arrythmias in a single centre adult congenital population. (6th June 2022) - Pennington, John William; English, Kate; Gardner, Sarah
Abstract : Introduction: AliveCor ECG tracing, is an established tool for detecting AF (atrial fibrillation) in acquired cardiology patients. It has not yet been assessed in adult congenital cardiology patients (ACHD). 24–48 hour Holter monitor tracing has variable rates of detection in paroxysmal symptoms, therefore newer technology is required to aid diagnosis.AimTo determine the utility of AliveCor detecting arrhythmias in ACHD patients, with paroxysmal cardiac symptoms. Methods: Retrospective analysis of AliveCor data over a two year period (2019–2021), at a single ACHD centre was performed (Leeds). AliveCor readings were reviewed by cardiologists and followed with a 12-lead ECG. Results: Of the 44 AliveCor devices, 36 (81%) were given for palpitations, 4 for dizziness, 2 for dyspnoea and 2 for syncope. 48% of patients (21) returned readings with palpitations, of which 11 (52%) had arrhythmias detected. Those identified include atrial fibrillation / flutter (6), atrial tachycardia / ectopy (3), PVC (2). 4 had sinus tachycardia only. This resulted in 22 interventions on 15 patients which included medication changes, cardioversions and electrophysiology studies on varying conditions (graph 1). 24–48 hour Holter Monitoring detection rate is between 5%-34%, and therefore inferior to AliveCor in this study. Conclusion: The role of AliveCor, provided by charity (CHSF), in congenital patients is bright but remains unclear. AliveCor is able to detect arrhythmias in this patient cohort, although only a small sample was assessed. A larger multicentre study would provide more clarification. This is likely to be more routine practice, with the young ACHD technological competent patients. Conflict of Interest: No